Meningkatkan Hasil Belajar Siswa Pada Materi Keberagaman Sosial Budaya Indonesia Dalam Mata Pelajaran Ilmu Pengetahuan Sosial Budaya (IPS) Dengan Menggunakan Media Gambar Di Kelas IV SDN Sukajaya I Koroncong Pandeglang - Miftahul Hasanah; Ade Farid Hasyim; Yeni Sulaeman; Ratna Dewi (KRAKATAU (Indonesian of Multidisciplinary Journals), 2023)
This study aims to improve learning outcomes on the subject of Indonesian socio-cultural diversity in socialstudies (IPS) subjects using media images in class IV SDN Sukajaya 1 Koroncong Pandeglang AcademicYear 2023/2024 This research is a classroom action research which includes four stages namely planning,action, observation, and reflection which consists of two cycles where each cycle is carried out in twomeetings. The subjects in the study were 25 grade IV students at SDN Sukajaya 1 Koroncong PandeglangRegency, consisting of 10 male students and 15 female students. The data collection instrument usesobservation sheets and tests. The data analysis technique used is descriptive qualitative and quantitativedescriptive analysis. The success of this research can be seen from the results of student learning which hasincreased in cycle I and cycle II.The results showed that there was an increase in student learning outcomes in Social Sciences (IPS) subjectmatter on Indonesian Socio-Cultural Diversity. The results of student learning completeness in cycle I,namely out of 25 students there were 7 students who had finished studying and there were 18 students whohad not finished studying. Whereas in cycle II there was an increase in learning outcomes, namely there were23 students or around 92% who had finished studying and who had not finished studying there were 2students. with the average score of students who experienced an increase in cycle I and cycle II, namely from60 to 80.4. There were positive changes in attitudes and activities in students during the learning process inaccordance with the results of observations during the class action. Based on the results of this study, it canbe concluded that social science learning outcomes (IPS) on socio-cultural diversity in class IV SDNSukajaya 1 through media images have increased and received a positive response from students.